IMPLEMENTATION OF BLUE OCEAN STRATEGY FOR LONG-TERM BUSINESS STRATEGY IN LAND TRANSPORTER COMPANIES IN INDONESIA - Harianto, Eric; Lookman, Cienthia (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Intense competition in business not only slashes profitability but can also cause a slowdown in the growth of a company. Moreover, the competitive advantage competitive strategy that is often used by many companies is no longer sustainable. The disruptive era makes efforts to maintain competitive advantage short-lived.The purpose of this research is to explore the Blue Ocean Strategy approach to be able to leverage the long-term business strategy for the land transporter company PT Lookman Djaja in order to become an innovative family company and continue to grow across generations. This research was conducted for six months starting from February 2021 to July 2021. The research was conducted using a qualitative descriptive method Creswell (2014) with informants consisting of 3 members of the board of directors, 3 employees from the marketing, accounting and operational divisions, along with 18 customers of PT Lookman Djaja who have a deep understanding of the company. Testing the data in this study was carried out using the data triangulation method. The results of this study are: 1) Strategy Canvas which provides an overview of the current conditions of the competitive arena: advantages and disadvantages of PT Lookman Djaja compared to its competitors, 2) ERRC matrix where PT Lookman Djaja can simultaneously eliminate, reduce, increase and create factors that offered to create value innovation, 3) Three paths from the Six Paths Framework that can be implemented by PT Lookman Djaja to reconstruct industry boundaries. In this research, finally found a new innovation strategy are warehousing service, multimode and information system. Keywords: Blue Ocean Strategy, Business Strategy, Land Transporter, Value Innovation, multimode.